Construction of a recombinant Lactobacillus casei expressing fliC gene fused with guanylyl cyclase C and dendritic cell-binding peptide using CRISPR–Cas9 system: a first step towards design of vaccine against colorectal cancer. Issue 2 (April 2021) - Khosravi, Azar Dokht; Teimoori, Ali; Seyed-Mohammadi, Sakineh
Abstract : N/A: Colorectal cancer (CRC) with 1.2 million new cases and 600 000 deaths per year is the 4th leading cause of cancer and the 2nd leading cause of cancer mortality worldwide. Effort to design of safe and efficient vaccines can be a good strategy for the treatment of primary or metastatic CRC. Plasmid pLCNICK was linearized by using restriction enzymes Bcu I and Apa I. Unintended fragments were removed from the plasmid and selected genes were cloned in plasmid. Electro-transformation of the two plasmids containing gRNA 1 and gRNA 2 into Lactobacillus casei was performed simultaneously in the following step. The recombinant L. casei was identified by PCR colony. For detection protein of interest was done Western blot. Amplification selected genes by PCR and then clone of fragments into two vectors were done successfully. After electroporation, growth of bacterial colonies on plates supplemented with antibiotic showed that the bacteria have received the plasmid because there was erythromycin resistance gene on plasmid. Also, the production of recombinant L. casei by CRISPR-Cas9 D10A nickase-based plasmid, and designed gRNA 1 and gRNA 2 was done successfully, and was confirmed by the presence of a 1126 bp band in agarose gel electrophoresis of colony PCR. Expression of the protein was shown by Western blot. In conclusion, recombinant lactic acid bacteria strains have the capacity to express heterologous proteins. Thus in this study for the first time a recombinant L. casei using CRISPR–Cas9 system as a first step for design of a vaccine against CRC was constructed that expresses fliC gene fused with guanylyl cyclase C and dendritic cell binding peptide.